Peer Social Support Relations with Student Academic Stress - Gilang Firnanda; Yulidar Ibrahim (Jurnal Neo Konseling, 2020)
Peer Social Support is a social support that is most needed by students in school. Social support received can make individuals feel more happy, cared for, loved and self-confidence arises. Support provided can be an individual protective factor to prevent and make him avoid academic stress. Academic stress is stress related to student learning activities in school, in the form of tensions experienced by students both the workload, work and student learning demands, so that it affects the physical, emotional, and student behavior. This study aims to reveal a picture of the relationship of peer social support with student academic stress in SMA Negeri 8 Padang. This research is a descriptive correlational study, with a sample of 130 students obtained using stratified random sampling techniques. Data collection instruments used a scale questionnaire which was compiled by itself in data collection using the Google forms application. The results of the study showed a significant negative direction and showed that social support for peers in students at SMA Negeri 8 Padang was in the moderate to high category, and in terms of stress Academic students are in the moderate to high category.